THE CONCEPT OF LEGAL JUSTICE FOR CHILDREN AS PERPETRATORS OF CRIMINAL ACTS OF NARCOTICS DISTRIBUTION (A Study of Decisions of The Medan District Court): A. The Concept of Legal Justice for Children as Perpetrators of Narcotics Trafficking Crimes, B. The Implementation of Legal Justice for Children as Perpetrators of Narcotics Trafficking Offenses in the Decisions of the Medan District Court, C. Obstacles in the Implementation of Legal Justice for Children as Perpetrators of Narcotics Trafficking - Ikhsan Sahriyan; Zulkarnain (Journal of International Islamic Law, Human Right and Public Policy, 2026)
This study examines the concept and implementation of legal justice for children involved in narcotics trafficking offenses within the Indonesian juvenile criminal justice system. Narcotics possess legitimate medical and scientific functions; however, their abuse and illegal distribution have resulted in serious social consequences, including the involvement of children as couriers or intermediaries in narcotics distribution networks. Children involved in such cases are generally not principal offenders, but rather victims of criminal exploitation, thereby requiring special legal protection based on the principle of the best interests of the child and restorative justice mechanisms. This research applies a normative legal research method through statutory and case approaches using descriptive-qualitative analysis. The findings reveal significant disparities in sentencing practices in several decisions of the Medan District Court involving children convicted of narcotics trafficking offenses. Despite similarities in the type of offense, category of narcotics, and quantity distributed, the punishments imposed varied considerably. The study concludes that judicial discretion, prosecutors’ indictments, subjective judicial considerations, and limited rehabilitation facilities remain dominant factors influencing court decisions. Therefore, strengthening juvenile justice regulations, improving law enforcement capacity, and providing adequate rehabilitation facilities are necessary to ensure optimal child protection and sustainable social reintegration.